A Decision Making PEMILIHAN LOKASI PENANGANAN PANTAI PROVINSI RIAU BERDASARKAN ANALYTICAL HIERARCHY PROCESS (AHP): ANALYTICAL HIERARCHY PROCESS (AHP) - Rizki Ramadhan Husaini (Racic : Rab Construction Research, 2019)
ABSTRACT Riau Province is one of the provinces that has several coastal areas, both in the mainland and the islands. The handling of many coastal locations in Riau Province is a problem for relevant agencies in making decisions about which coastal locations will be prioritized for handling. This study analyzes the level of coastal vulnerability and decision-making systems in terms of determining the priority of coastal areas to be handled using the Analytical Hierarchy Process (AHP) method. The results showed that Tanjung Motong beach, Kepulauan Meranti Regency and Coastal Pambang Beach in Bengkalis Regency were the highest vulnerability beaches with a value of 244.95. The criteria for strategic issues with sub-criteria for national strategic areas have the highest level of influence for determining the priority of coastal handling areas, which is 73%. Coastal Pambang Beach in Bengkalis Regency is a coastal area that is located in a national strategic area that gets priority handling. Keywords: Beach, Vulnerability, Priority, Criteria, Analytical Hierarchy Process (AHP)